Effect of Sodium Chloride on Leptospirillum Ferriphilum Dsm 14647(T) and Sulfobacillus Thermosulfidooxidans Dsm 9293(T): Growth, Iron Oxidation Activity and Bioleaching of Sulfidic Metal Ores - Levican-Jaque, G (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
In bio-hydrometallurgical operations, several studies found that besides having inhibitory effects chloride may also enhance the bacterial leaching of metal sulfides. This study compares the effect of chloride on bacterial growth, iron oxidation activity and bioleaching performance of Leptospirillum ferriphilum and Sulfobacillus thermosulfidooxidans. The exposure to elevated NaCl concentrations affected cell growth and iron oxidation rate in both strains. Sb. thermosulfidooxidans showed better tolerance to NaCl than L. ferriphilum, with the concentration that inhibited biological iron oxidation and bacterial growth completely being 325 mM and 525 mM NaCl for L ferriphilum and Sb. thermosulfidooxidans, respectively. At 100 mM NaCl, cell growth and iron oxidation of L. ferriphilum were severely slowed down while for Sb. thermosulfidooxidans, in contrast, they appeared almost unaffected. Additionally, while only 22% of L. ferriphilum cells survived after 18 h exposure to 100 mM NaCl, viability of Sb. thermosulfidooxidans was not strongly affected by 300 mM NaCl. Bioleaching of chalcopyrite and sphalerite were studied. For chalcopyrite, bioleaching by Sb. thermosulfidooxidans in the presence of 200 mM was similar to its performance in the absence of NaCl. However, bioleaching by L. ferriphilum was reduced by 50% in the presence of 200 mM NaCl. For sphalerite, bioleaching by both bacteria, L. ferriphilum and Sb. thermosulfidooxidans, was inhibited significantly in the presence of 200 mM NaCl. This study indicates that Sb. thermosulfidooxidans will be more suitable than L. ferriphilum to operate bioleaching with high chloride concentrations. Additionally, since bioleaching performance of chalcopyrite differed from bioleaching of sphalerite under similar conditions, further investigations on bioleaching with different sulfidic minerals in the presence of chloride ions are necessary.